Persistent cough as a paraneoplastic presenting symptom in six patients with renal cell carcinoma - Vinay R. Patel; Bradley A. Morganstern; Louis R. Kavoussi (Asian Journal of Urology, 2017)
Objective: With today's modern imaging modalities, patients diagnosed with renal cell carcinoma (RCC) rarely present symptomatically. In some cases, however, they can develop paraneoplastic syndromes with associated symptoms. To date, only three cases of RCC presenting with chronic dry cough have been reported. We describe six patients who presented with cough that improved following radical nephrectomy. Methods: A retrospective review of patients undergoing partial or radical nephrectomy for renal masses between January 2015 and March 2016 was performed, and patients presenting with a cough were examined. Results: Six patients presented with chronic cough and were discovered to have a large renal mass. Postoperative spontaneous resolution of cough was noted in all but one patient, in whom coughing was reduced and limited to the mornings. Cough duration ranged from 3 months to just over a year. All patients were treated with radical nephrectomy, which was cytoreductive in four patients. Average tumor size was 10.9 cm (SD = 2.2 cm). Five of the tumors had clear cell pathology, and every tumor was Fuhrman grade IV, unifocal, and demonstrated necrosis. Sarcomatoid features were reported in four of the tumors. Conclusion: Our study presents the largest series of patients with RCC who presented with a chronic cough that was significantly improved following radical nephrectomy. We believe the cause of cough is multifactorial and further investigation is needed to clearly elucidate the etiology.